Cardiovascular reactivity as a measure of irritability in a transdiagnostic sample of youth: Preliminary associations. Issue 4 (13th August 2021) - Naim, Reut; Goodwin, Matthew S.; Dombek, Kelly; Revzina, Olga; Agorsor, Courtney; Lee, Kyunghun; Zapp, Christian; Freitag, Gabrielle F.; Haller, Simone P.; Cardinale, Elise; Jangraw, David; Brotman, Melissa A.
Abstract: Objectives: Irritability is a transdiagnostic symptom in developmental psychopathology, conceptualized as a low threshold for frustration and increased proneness to anger. While central to emotion regulation, there is a vital need for empirical studies to explore the relationship between irritability and underlying physiological mechanisms of cardiovascular arousal. Methods: We examined the relationship between irritability and cardiovascular arousal (i.e., heart rate [HR] and heart rate variability [HRV]) in a transdiagnostic sample of 51 youth ( M  = 12.63 years, SD = 2.25; 62.7% male). Data was collected using the Empatica E4 during a laboratory stop‐signal task. In addition, the impact of motion activity, age, medication, and sleep on cardiovascular responses was explored. Results: Main findings showed that irritability was associated with increased HR and decreased HRV during task performance. Conclusions: Findings support the role of peripheral physiological dysregulation in youth with emotion regulation problems and suggest the potential use of available wearable consumer electronics as an objective measure of irritability and physiological arousal in a transdiagnostic sample of youth.